2009
DOI: 10.1097/ccm.0b013e3181930026
|View full text |Cite
|
Sign up to set email alerts
|

Saline instillation before tracheal suctioning decreases the incidence of ventilator-associated pneumonia*

Abstract: Instillation of isotonic saline before tracheal suctioning decreases the incidence of microbiological proven VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 38 publications
2
68
0
9
Order By: Relevance
“…Caruso et al 7 found that routine suctioning based on indications described in the guidelines 1 of the American Association of Respiratory Care, along with instillation of physiological saline, reduced the risk for ventilatorassociated pneumonia by 54% in a sample of critically ill patients. The authors 7 hypothesized that suctioning and/or coughing induced after the instillation of physiological saline may have contributed to the reduced risk for infection. Blamoun et al 8 included regular endotracheal suctioning, defined as suctioning every 4 hours, as part of an expanded ventilator bundle and were successful in reducing the rates of ventilator-associated pneumonia to zero.…”
Section: Introductionmentioning
confidence: 99%
“…Caruso et al 7 found that routine suctioning based on indications described in the guidelines 1 of the American Association of Respiratory Care, along with instillation of physiological saline, reduced the risk for ventilatorassociated pneumonia by 54% in a sample of critically ill patients. The authors 7 hypothesized that suctioning and/or coughing induced after the instillation of physiological saline may have contributed to the reduced risk for infection. Blamoun et al 8 included regular endotracheal suctioning, defined as suctioning every 4 hours, as part of an expanded ventilator bundle and were successful in reducing the rates of ventilator-associated pneumonia to zero.…”
Section: Introductionmentioning
confidence: 99%
“…14 One recent study 15 in adults showed fewer cases of microbiologically proven VAP when saline instillation occurred before suctioning (relative risk reduction, 54%) and no association between saline use and endotracheal tube obstruction. Other respiratory interventions such as physiotherapy may have contributed to a reduction in their VAP rate.…”
Section: Discussionmentioning
confidence: 99%
“…Caruso's 2009 study of 262 adult patients found a VAP risk reduction of 54% with routine saline instillation. 61 A limitation of that study may be that HMEs were utilized to provide humidification, possibly necessitating saline instillation for secretion thinning.…”
Section: Saline Instillationmentioning
confidence: 99%